Temperature-compensated oscillations in respiration and cellular protein content in synchronous cultures of Acanthamoeba castellanii. - Lloyd, D (1982)
Synchronous cultures of the soil amoeba Acanthamoeba castellanii, established by a selection procedure, show significant oscillations of respiration and total cell protein. There was little difference between the period of these oscillations, which averaged 76 min, although the five incubation temperatures used varied between 20 degrees C and 30 degrees C and the cell division time increased from 7.8 to 16 hr. The phase of these oscillations also corresponded approximately at all incubation temperatures. Similar observations made over the whole division cycle at three temperatures indicated that similar oscillations occurred, with a constant period of 65 min, although these data were too variable to show this unequivocally. Control (asynchronous) cultures show that the oscillations are not a consequence of metabolic perturbation produced by the centrifugal selection procedure. It is suggested that these temperature-compensated epigenetic oscillations serve a dual role in cell cycle and circadian timekeeping and that cell cycle time is quantized.